Activity levels of po in the coastal area of Kapar, Malaysia, close to a coal-fired power plant - Asnor Azrin Sabuti,; Che Abd Rahim Mohamed, (Universiti Kebangsaan Malaysia, 2012)
The activity concentration of 210Po from six different samples consisting of raw charcoal, surface sediment, rainwater (suspended solids (SSrw) and dissolved phase (Drw) and estuarine water (suspended solids (SSew) and dissolved phase (Dew)), were analyzed. The activity concentration of 210Po in solid samples was between 7.63 ± 0.67 and 744.28 ± 21.12 Bqkg-1 and in dissolved samples varied between 0.34 ± 0.03 and 86.33 ± 6.51 mBqL-1. On average, 210Po activity in SSrw sample was the highest, at nearly three times its original form (charcoal). SSew and surface sediment samples were similarly distributed between 15th March and 1st August samplings, but were relatively lower than charcoal and SSrw samples. The natural meteorological variability also enhanced 210Po distribution and dispersion to a few kilometers from the coal-fired power plant.